FEASIBILITY STUDY OF MARKETING BERKATUL BLISS AS A LOW-GLYCEMIC FOOD FOR PEOPLE WITH DIABETES - Chintya Paramita Puspita; Soenar Soekopitojo; Ababil Karhoma Wijaya (RADJA PUBLIKA, 2025)
This study aims to analyze the marketing feasibility of Berkatul Bliss, a healthy snack made from rice bran designed for people with diabetes. Amid increasing demand for functional foods, it is essential to develop local products that are both nutritious and competitive in the market. This research employed a descriptive approach using qualitative and quantitative methods through consumer surveys, focus group discussions (FGDs), and analysis of marketing mix strategies (product, price, distribution, promotion). The results show that Berkatul Bliss possesses high appeal in terms of product quality, packaging, and its functional value as a low-glycemic food. Consumer acceptance was notably positive, especially regarding health benefits, informative packaging, and affordable pricing. The marketing strategy based on local ingredients proved effective in enhancing the product's competitiveness. These findings support contributions to the Sustainable Development Goals (SDGs), particularly SDG 2 (food security), SDG 3 (health and well-being), and SDG 8 (economic growth). The study recommends an integrated and educational marketing strategy as a long-term approach to developing local functional food products.